TEACHERS’ PERCEPTIONS TOWARDS THE UTILIZATION OF DIGITAL LEARNING MATERIALS IN EFL TEACHING AND LEARNING - Monitha Geraldine (STBA Pontianak, 2018)
The aim of the research was to find out the teachers’ perceptions towards the utilization of digital learning materials in EFL teaching and learning. The term digital learning material was used in this research to refer to materials included in the context of a course that support the students’ achievement of the describe learning goals. The use of E-book as one of the digital learning materials became the main focus of this research. The subjects of the research were the English teachers of SMK LKIA and SMK 5 in Pontianak. A descriptive research design was implemented to achieve the purpose of this study. The writer utilized the structured questionnaires and interviews to collect the data. In analyzing the data, the writer used qualitative analysis of interactive models. Based on the findings of the study, most of the English teachers in SMK LKIA and SMK 5 Pontianak have already integrated digital learning materials in their EFL teaching eventhough they still need to improve their knowledge to use another PDF softwares to support their teahing. In addition, the English teachers in SMK LKIA and SMK 5 Pontianak also showed positive attitude towards the utilization of digital learning materials.